Functionalization of titania nanotubes with electrophoretically deposited silver and calcium phosphate nanoparticles: Structure, composition and antibacterial assay; Materials Science and Engineering: C; Vol. 97 - Chernozem R. V. Roman Viktorovich; Surmeneva M. A. Maria Alexandrovna; Krauze B. Barbel; Baumbach T. Tilo; Ignatov V. P. Viktor Pavlovich; Primak O. Oleg; Loza K. Katerina; Epple M. Mattias; Ennen F. Franka; Vittmar A. Aleksandra; Ulbrikht M. Mattias; Chudinova E. A. Ekaterina Aleksandrovna; et al. (2019, 2019)
Title screen